PENGGUNAAN MEDIA DADU ANGKA BERWARNA MENINGKATKAN KEMAMPUAN LITERASI NUMERASI ANAK USIA 4-5 TAHUN RA RAUDLATUL ISLAMIYAH TAHUN PELAJARAN 2025/2026 - Khoirunnisa; Asri Widiatsih; Syamsul Muarif (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The research entitled "Colored Number Dice Media Improves Numeracy Literacy Skills of 4-5 Year Old Children at RA Raudlatul Islamiyah in the 2025/2026 Academic Year". The research was motivated by the low numeracy literacy skills of children, where most children are not yet able to recognize number symbols, count objects correctly, and understand the relationship between numbers and quantities in concrete terms. The general objective of this research is to improve children's numeracy literacy skills through the use of colored number dice media as a fun and meaningful learning tool. The specific objectives of this research are (1) to describe the application of colored number dice media in numeracy learning for children aged 4-5 years, and (2) to determine the increase in children's numeracy literacy skills after the application to determine the increase in children's numeracy literacy skills after the implementation of the media. The method used is Classroom Action Research (CAR) with the Kemmis and McTaggart model consisting of four stages, namely planning, action implementation, observation, and reflection. The research subjects were 16 children in group A at RA Raudlatul Islamiyah in the 2025/2026 academic year. Data collection techniques included observation and documentation. Data were analyzed descriptively qualitatively and quantitatively through a comparison of the results of pre-action, cycle I, and cycle II. The output of this study is an increase in early childhood numeracy literacy skills, especially in recognizing numbers, counting objects, and matching numbers with quantities. In addition, this study produced innovative learning media in the form of colored number dice that can be used by PAUD teachers as an alternative media in developing children's numeracy skills in a fun and contextual way.